2021
DOI: 10.3390/ijms22115946
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Modeling of Fibrinogen Adsorption onto LiNbO3 Single Crystal–Single Domain Surfaces

Abstract: For the development of next-generation protein-based biosensor surfaces, it is important to understand how functional proteins, such as fibrinogen (FBG), interact with polar substrate surfaces in order to prepare highly sensitive points of medical care diagnostics. FBG, which is a fibrous protein with an extracellular matrix, has both positively and negatively charged regions on its 3-dimensional surface, which makes interpreting how it effectively binds to polarized surfaces challenging. In this study, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…32 Another study has shown that the nickel modification can improve the adsorption of water molecules on anatase-TiO 2 , rutile-TiO 2 , and ZnO photoanodes, enhancing their photoelectrochemical performance. 61 Particularly, Adsorption Locator for modelling has been broadly used for evaluating the adsorption interaction or non-bonded energies of organic and water molecules for various applications, including biomolecule/surface interactions, 62 adsorption of SiF 4 and HF gaseous molecules at the molecular level, 63 next-generation protein-based biosensor surfaces, 64 catalyst/adsorbents for oil recovery and viscosity reduction process, 65 drug delivery tool in biological systems, 66 etc. Here, the influence of the Al 3+ –Mg 2+ dual substitution on the adsorption of water molecules on the BaTaO 2 N(110) surfaces was also explored by combined Molecular Dynamics and Monte-Carlo computer simulation.…”
Section: Resultsmentioning
confidence: 99%
“…32 Another study has shown that the nickel modification can improve the adsorption of water molecules on anatase-TiO 2 , rutile-TiO 2 , and ZnO photoanodes, enhancing their photoelectrochemical performance. 61 Particularly, Adsorption Locator for modelling has been broadly used for evaluating the adsorption interaction or non-bonded energies of organic and water molecules for various applications, including biomolecule/surface interactions, 62 adsorption of SiF 4 and HF gaseous molecules at the molecular level, 63 next-generation protein-based biosensor surfaces, 64 catalyst/adsorbents for oil recovery and viscosity reduction process, 65 drug delivery tool in biological systems, 66 etc. Here, the influence of the Al 3+ –Mg 2+ dual substitution on the adsorption of water molecules on the BaTaO 2 N(110) surfaces was also explored by combined Molecular Dynamics and Monte-Carlo computer simulation.…”
Section: Resultsmentioning
confidence: 99%